PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCABULAN ANAK STUDI KASUS WILAYAH KEPOLISIAN RESOR KOTA PEKANBARU - Yulius Wibisono Prakosa Putro; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Children are the future of the nation and the next generation for theideals ofnation-building, so that every child has the right to survival, growthand development, creation, participation, and is entitled to protection fromacts of violence and discrimination as well as civil rights and freedoms.Sexual crimes against children as victims really feel very sad to hear,especially with the current developments that have made the situation worse.One of the causes of child sexualabuse is the easy access to pornographicvideos on the internet, which creates a desire for those who watch them, sothat children are often used as an outlet for watching them. The aims of thisthesis research are: First to find out law enforcement against the CriminalAct of Child Abuse in the Case Study of the Pekanbaru City Resort Police,Second to find out the obstacles to the Criminal Actof Child Abuse in theCase Study of the Pekanbaru City Resort Police.This type of research is classified as sociological legal research. Thislegal research was conducted at the Pekanbaru Police, while the populationand sample were all parties related to the problem under study. The datasources used are primary, secondary, and tertiary data, while the datacollection technique uses interviews and literature review.From the results of the research problem, there are two conclusionsthat can be drawn, namely: First, law enforcement against criminal acts ofobscenity in the jurisdiction of the Pekanbaru City Police, the police alwaysprocess every obscenity case that comes to trial. Second, obstacles thathinder law enforcement against criminal acts of child molestation in thejurisdiction of the Pekanbaru City Police because these children receivethreats from the perpetrators so that these children do not dare to tell whathappened to other people.Keywords: Law Enforcement - Criminal - Obscenity